2015
DOI: 10.4292/wjgpt.v6.i3.28
|View full text |Cite
|
Sign up to set email alerts
|

Current position of vasoconstrictor and albumin infusion for type 1 hepatorenal syndrome

Abstract: Spontaneous bacterial peritonitis (SBP), refractory ascites, hepatorenal syndrome (HRS), hyponatremia and hepatic encephalopathy are complications which frequently happen during a clinical course of decompensated cirrhosis. Splanchnic and peripheral vasodilatation, increased intrarenal vasoconstriction and impaired cardiac responsive function are pathological changes causing systemic and hemodynamic derangement. Extreme renal vasoconstriction leads to severe reduction of renal blood flow and glomerular filtrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…At present, global scholars have not fully understood the pathogenesis of HRS. Existing studies have found that due to the influence of end-stage liver diseases such as cirrhosis, the inactivation of vasodilator factors in vivo is reduced, which leads to the dilation of visceral and peripheral arteries, the contraction of renal vessels, the reduction of glomerular filtration rate and the decrease of renal blood flow, and finally the occurrence of HRS ( Sobhonslidsuk, 2015 ; Simonetto et al, 2020 ; Wu et al, 2024 ). At the same time, liver inflammation, intestinal flora displacement and concurrent infection caused by cirrhosis lead to the release of a large number of inflammatory factors and endotoxemia, causing renal microcirculation dysfunction, which can induce renal function injury ( Rad et al, 2024 ).…”
Section: Understanding Liver Cirrhosis In Modern Medicinementioning
confidence: 99%
“…At present, global scholars have not fully understood the pathogenesis of HRS. Existing studies have found that due to the influence of end-stage liver diseases such as cirrhosis, the inactivation of vasodilator factors in vivo is reduced, which leads to the dilation of visceral and peripheral arteries, the contraction of renal vessels, the reduction of glomerular filtration rate and the decrease of renal blood flow, and finally the occurrence of HRS ( Sobhonslidsuk, 2015 ; Simonetto et al, 2020 ; Wu et al, 2024 ). At the same time, liver inflammation, intestinal flora displacement and concurrent infection caused by cirrhosis lead to the release of a large number of inflammatory factors and endotoxemia, causing renal microcirculation dysfunction, which can induce renal function injury ( Rad et al, 2024 ).…”
Section: Understanding Liver Cirrhosis In Modern Medicinementioning
confidence: 99%